Penetapan Masa Jabatan Jaksa Agung dalam Sistem Penetapan Jabatan Pejabat Negara - Titik Triwulan Tutik (Fakultas Hukum Universitas Islam Indonesia, 2011)
This research is to examine on how the rules of law that have ever been applied to regulate the determination of term of office of an attorney general and its relationship to the system in determining the position of a state official. The research is dogmatic supported by a historical approach, statute approach, and comparative approach. The steps of the research were conducted by collecting the materials of secondary law, all of which were noted using card system based on the subjects of research problems and the writing system. The result of the research shows that the position of the attorney is between two sides – judicative and executive. As a result, it could emerge a contradiction in its regulation (dual obligation). Related to the term of office, it is found that no regulation of the Attorney of Indonesia Republic regulates about the term of office of an attorney general either definitively or restrictively. The determination of a term of office of an attorney general commonly follows the constitutional convention saying that an attorney general is appointed at the beginning of cabinet and will end by ending of the term of the office.